Guidelines for Industrial Business Management During a Flood Disaster - Sukkasem, Wirattana; Bua-In, Dr. Nopporn; Sincharu, Dr. Thanin (Migration Letters, 2023)
Floods continually impact the industrial economy in Thailand almost every year, making flood response crucial for preventing harm to employees and the organization’s property, as well as ensuring continuous business operations. This research aims to study the management practices of industrial business organizations during flooding and develop a structural equation model, combining qualitative and quantitative research methods. Qualitative research involved 9 experts and a group discussion with 11 participants, while quantitative data was gathered from questionnaires distributed to 500 executives in the industrial business sector who had experienced flooding. Descriptive statistics, inferential statistics, and multiple statistics were used for analysis. The research findings indicate that guidelines for managing industrial business organizations during flooding prioritize four elements in the following order of importance: 1) Risk management components (X̄ = 4.35): Most important items: Following announcements from the Meteorological Department regarding the continuous rain situation. 2) Organizational management components (X̄ = 4.32): Most important items: Preparing a list of emergency telephone numbers to contact various agencies for assistance during floods. 3) Cooperative management components (X̄ = 4.24): Most important items: Collaborating with personnel in the organization to prevent flooding, such as working together to fill sandbags and build waterproof embankments. 4) Resource management components (X̄ = 4.20): Most important items: Establishing a gathering point for emergency employee evacuation. Regarding the hypothesis test results, it was found that industrial businesses located within industrial estates and industrial businesses located outside industrial estates giving importance to the management practices of industrial business organizations during flooding is not significantly different at the 0.05 level for industrial businesses located outside industrial estates. The results of the analysis of the developed structural equation model revealed that it met the evaluation criteria and was consistent with the empirical data. It obtained a chi-square probability level value of 0.058, a relative chi-square value of 1.160, a concordance index value of 0.959, and a root mean square error of approximation index value of 0.018. Guidelines for Industrial Business Management During a Flood Disaster encompass four key aspects: Risk Management, Collaboration Management, Organizational Management, and Resources Management, each of which holds significant importance. The results of the hypothesis testing revealed that the Risk Management component significantly influences the Collaboration Management segment, with the highest weight value (Standardized Regression Weight) at 0.83. This empirical data emphasizes the necessity for organizational risk management to garner support and participation from all levels within the organization.